2016
DOI: 10.1182/bloodadvances.2016000976
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of idelalisib with rituximab and/or bendamustine in patients with recurrent indolent non-Hodgkin lymphoma

Abstract: Key Points Combining phosphatidylinositol-3-kinase δ inhibition with rituximab, bendamustine, or both is feasible and active in relapsed iNHL. The safety of novel combinations should be proven in phase 3 trials before adoption in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This isoform is almost specific to hematopoietic cells and seems to play a minor role in platelet activation. The first-in-class oral selective inhibitor of p110δ isoform Idelalisib has been approved for the treatment of hematological malignancies including chronic lymphocytic leukemia (CLL), follicular B-cell non-Hodgkin lymphoma (FL), and small lymphocytic lymphoma (SLL) [ 15 , 16 ], and has shown considerable antitumor activity in the treatment of hematological cancer [ 17 ]. In this respect, Idelalisib is currently combined with rituximab as a second-line agent in intractable patients or patients with other co-morbidities [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This isoform is almost specific to hematopoietic cells and seems to play a minor role in platelet activation. The first-in-class oral selective inhibitor of p110δ isoform Idelalisib has been approved for the treatment of hematological malignancies including chronic lymphocytic leukemia (CLL), follicular B-cell non-Hodgkin lymphoma (FL), and small lymphocytic lymphoma (SLL) [ 15 , 16 ], and has shown considerable antitumor activity in the treatment of hematological cancer [ 17 ]. In this respect, Idelalisib is currently combined with rituximab as a second-line agent in intractable patients or patients with other co-morbidities [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the combination of idelalisib plus lenalidomide and rituximab in FL and MCL resulted in >70% treatment discontinuation [ 61 ]. A phase 1 study of idelalisib with rituximab and/or bendamustine demonstrated high response rates in heavily treated R/R B-NHL, although later phase trials showed an increase in toxicity not evident in the original phase 1 [ 62 ]. Other combination studies include idelalisib in combination with obinutuzumab in FL (NCT03890289) or WM [ 63 ], duvelisib with acalabrutinib in B-NHL (NCT04836832), umbralisib with rituximab in FL/MCL (NCT03919175), with ublituximab in FL (NCT03828448) or with ublituximab-CHOP in MCL (NCT04692155).…”
Section: Review Of Approved Small Molecule Inhibitorsmentioning
confidence: 99%
“…however, due to the potential for serious toxicities in combinations with idelalisib, the authors warn of the necessity to perform phase 3 studies to rule out any possible toxicities. 71 Dactolisib in combination with abiraterone acetate or everolimus has been investigated in phase 1 studies in patients with solid malignancies; however, both studies reported poor tolerability at the doses tested. 72,73 Many clinical trials incolving dactolisib have been withdrawn or teminated, with no currently ongoing trials registered on ClinicalTrials.gov (accessed 05 June 2020).…”
Section: Rationale For Combination Treatmentmentioning
confidence: 99%